DETERMINAN KEBUTUHAN SAK ETAP BAGI UKM (Studi Empiris Pada UKM Makanan di Kota Semarang) - Faizatuz Zahro; Sri Dewi Wahyundaru (Conference In Business, Accounting, And Management (CBAM), 2015)
SAK ETAP level needs for SMEs is very low and also still considered burdensome SMEs. The study entitled "Determinan Kebutuhan SAK ETAP  bagi UKM" tested several factors that affect the need for SMEs SAK ETAP. These factors are the owner of educa tion, understanding   of   information   technology,   the   qualitative   characteristics   of   financial statements, socialization SAK ETAP and sca le. This study used a descriptive research. Data collection was conducted by questi onnaire to 42 owners of SMEs Food in Semarang.  The data obtained were analyzed using SPSS. Mechanical analysis using validity, reliability test, normality test, mu ltico llinearity, heteroscedasticity  test, multiple  linear regression  test, t test, F test, and the coefficient  of de termina tion. The  analysis  showed  that  all  items  are  valid  question.  Overall  variable  is declared reliable. Normally distributed regression model, did not happen multikolinier and heteroscedasticity. The regression coefficient is positive. Hypothesis testing results show that the education owner (X1), Qualitative Characteristics of Financial Statements (X3) and Scale (X5) significantly  affects  SAK ETAP  needs  for SMEs,  while  Understanding  Informati on Technology (X2) and Socialization SAK ETAP (X4) had no significant effect needs to SAK ETAP for SMEs. Taken together, all the independent variables affect the SAK ETAP needs. Determination coefficient of 53.60%.     Keywords:  business  scale,  information  technology,  owner  education,  socialization,   SAK ETAP